(untitled) (Interdisciplinary Studies Journal, 2024)
In the current digital age, the profusion of technological devices presents challenges to student learning due to the many distractions. Finding innovative ways to make learning more meaningful, increase student engagement, and ensure knowledge retention is critical. The question arises of how to take advantage of these technologies as constructive tools in education. This study explores the application of technological practices in learning, evaluating applications that can be integrated to help teachers in educational activities. In particular, the research focuses on applications that make use of augmented reality (AR) technology, investigating how this approach can transform classroom dynamics. The methodology used is qualitative and exploratory. The results indicate that the introduction of technological approaches in teaching promotes a more meaningful interaction between teachers and students, stimulating collaboration and the exchange of information, making the teaching-learning process more relevant. Additionally, the inclusion of AR applications encourages active student participation, simplifies understanding of abstract concepts, and enhances problem solving. In summary, this study highlights how the adoption of technological approaches can enrich the educational experience, encouraging student engagement and facilitating learning.